2021
DOI: 10.1002/solr.202000811
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sodium Diethyldithiocarbamate to Enhance the Open‐Circuit Voltage of CH3NH3PbI3 Perovskite Solar Cells

Abstract: The incorporation of additives to modulate the properties of metal halide perovskite thin films has become a successful approach in improving the power conversion efficiency of perovskite‐based solar cells. Herein, the beneficial use of sodium diethyldithiocarbamate (NaDEDTC) as processing agent in improving the open‐circuit voltage of methylammonium lead triiodide perovskite solar cells is reported. DEDTC reduces the rate of perovskite crystallization. Absorption and emission spectra show that the optical ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Compared the results of AAD with PbI 2 -AAD, it is found that the missing hydrogen atoms and the 1 H resonance signal shifting to high frequency are due to the formation of Pb-O coordination bond and N-H…N hydrogen bond after annealing at 100 °C. [39,41] These can also be corroborated by the XPS and FT-IR measurements. From the XPS measurements (Figure 2g; Figure S7, Supporting Information), the binding energies for Pb 4f and O 1s si-multaneously upshift 0.1 eV.…”
Section: Interface Interaction Mechanismsupporting
confidence: 59%
“…Compared the results of AAD with PbI 2 -AAD, it is found that the missing hydrogen atoms and the 1 H resonance signal shifting to high frequency are due to the formation of Pb-O coordination bond and N-H…N hydrogen bond after annealing at 100 °C. [39,41] These can also be corroborated by the XPS and FT-IR measurements. From the XPS measurements (Figure 2g; Figure S7, Supporting Information), the binding energies for Pb 4f and O 1s si-multaneously upshift 0.1 eV.…”
Section: Interface Interaction Mechanismsupporting
confidence: 59%
“…The most representative band of ADDC corresponds to the CS stretching at 985 cm −1 . [ 31 ] In addition, some other characteristic bands such as CS stretching (≈1100 cm −1 ) are useful. [ 32 ] In Figure S11 (Supporting Information), only marginal differences were observed between the IR wavenumbers of the control films and the films with different concentrations of ADDC.…”
Section: Resultsmentioning
confidence: 99%
“…The Pb 4f peaks shifted from 137.5 eV (4f 7/2 ) and 142.3 eV (4f 5/2 ) to 138.2 and 143.1 eV for the control and DADA-treated perovskite thin films, respectively. The binding energy of Pb core levels in perovskite film increased, implying greater binding of anions and cations on the perovskite surface, which might be induced by strong binding between surface ions and DADA. , Figure c shows the XPS I 3d spectra of the control and DADA-treated perovskite thin films. The I 3d peaks shifted from 618.3 eV (3d 5/2 ) and 629.8 eV (3d 3/2 ) to 619.0 and 630.4 eV for the control and DADA-treated perovskite thin films, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their ionic properties, which are related to organic-cation and halide vacancies and uncoordinated lead and iodine ions, perovskites contain various defects, which are often mainly concentrated at grain boundaries and on perovskite surfaces. These defects capture charges, which generates nonradiative recombination and hysteresis and, thus, affects the device performance. In addition, defects promote ion migration and charge accumulation in the device, which destroys the device structure and considerably reduces both the device stability and performance. In the early development of PSCs, researchers mainly focused on the improvement of the perovskite active layer by engineering components, , optimizing fabrication processes, , engineering solvents, , and modifying interfaces by passivating defects to reduce the defect densities of perovskite active layers. Interfacial modification is a facile and effective method for reducing the number of surface defects.…”
Section: Introductionmentioning
confidence: 99%